Melhoramento intrapopulacional do maracujazeiro azedo mediado por procedimentos clássicos - Fachi, Leandro Rafael (2022)
The advance of genetic improvement in passion fruit allowed the development of new cultivars, adapted to the different soil and climatic conditions of the country, thus improving productivity, and contributing to the increase of producers' income. However, for the success and continuity of a genetic improvement program, it is necessary to identify the genetic variability, which allows the identification of superior genotypes and the establishment of strategies to maintain the variability in the population. Another important factor in selection is knowledge of the relationship between characters. However, as many characteristics are taken into account in the selection process, the analysis of all information can be difficult and costly, in this sense, the use of correlation network analysis is a technique that can be used to assist in this task. Thus, the objectives of this study were to develop a new variety and monitor population variability in order to establish strategies for Unemat's sour passion fruit breeding program. Genotypes of full-sib families in the third cycle of recurrent intrapopulation selection of the Unemat genetic improvement program were evaluated, and morphoagronomic traits related to flower and fruit were evaluated. Thus, through this study, it was possible to develop the cultivar Solar, which is adapted to the edaphoclimatic conditions of the State of Mato Grosso and stands out for the production of pulp, which has a dark orange color with a high content of total soluble solids (14.7 oBrix ) and provides a pulp yield of around 40%, making it an excellent choice for both fresh consumption and industry. It was found that there is still variability to be explored in the population, and the Ward-MLM procedure allowed the identification and formation of three groups. Among the groups formed, group I had the highest averages for the variables related to flower, group II had the highest values for the variables related to productivity and group III had the highest averages for the variables related to fruit quality. Among the variables, androgynophore length, nectar chamber length, anther surface, nectar chamber length and stigma surface were the variables that most contributed to the divergence between the evaluated genotypes. Through the use of the correlation network, it is possible to verify the ease of visual observation of the relationships between the characteristics, being observed the greatest correlations between the characteristics flower petal length x sepal length, flower petal length x nectar chamber length x a anther surface and sepal length x nectar chamber length to anther surface. It was also possible to observe that the CA and CNSA characteristics presented greater centrality in the network constituted by all groups of characteristics, being these the main characteristics that the breeder must take into account in the genetic improvement program, which are of paramount importance in directing the program to the next selection cycles.